Способы применения новой экономической критики. Случай «Подростка» Ф. Достоевского - КИСЕЛЮТЕ, ИНГРИДА (SlavVaria, 2021)
Application of The New Economic Criticism. Case of “The Raw Youth” by F. Dostoevsky. First of all Dostoevsky’s novel “The Raw Youth” attracts our attention with its abundance of themes and, as noted, big amount of research (in comparison with other works).It is interesting that in all studies and encyclopedias the main character of this novel, Arkady Dolgorukij, is said that his main idea is “to become a Rothschild.” The idea of the main character becomes a key component in understanding his actions and his main attribution. However, the idea, which is vaguely explained by the character himself at the very beginning of the work is lost not only in the further narration, but also in the generally accepted characterization of the protagonist. The article mainly analyzes the metaphorical idea of the main character of the novel “The Raw Youth” “to become a Rothschild”, and attempts to find out and show why in the history of literature the idea of the protagonist in Dostoevsky’s novel “to become a Rothschild” can be considered as a hypertextual element of entire Dostoevsky’s poetics.